Independent impacts of co-formulants contained in anthelmintic formulations on seed germination of grassland species - Eichberg, Carsten; Laber, Lars; Jaß, Scarlett; García, Andrés; Donath, Tobias (Elsevier, 2026)
Agrochemicals have been shown to affect non-target organisms and are often applied as mixtures of active ingredient and co-formulants. Although there is evidence that co-formulants play a role in these effects, their contribution has hardly been studied. Therefore, we studied effects of co-formulants on seed germination (percentage, time, synchrony) using a common anthelmintic formulation. The seeds of four species of temperate grasslands (Achillea ptarmica, Agrostis capillaris, Dianthus deltoides, Plantago lanceolata) were exposed to a commercial moxidectin formulation at a concentration of 10 mg l−1 as well as three of its co-formulants: benzyl alcohol (BA), butylated hydroxytoluene (BHT) and disodium ethylenediamine tetraacetic acid (EDTA-Na2). Results showed that the tested anthelmintic formulation as a whole and two of its co-formulants (BA, BHT) as individual substances significantly impacted germination behaviour of the test species. Formulation, BA and BHT significantly reduced germination percentage in all species compared to the control, with BA exerting the strongest effect (reduction up to 99 %). The same three treatments significantly increased mean germination time in all species by a factor of two to four. Germination synchrony showed a weaker response and was only affected in two species (A. capillaris, D. deltoides) and only by BHT (reduction of 49 % and 60 %, respectively). The strong effects of BA and BHT on seed germination suggest that their contribution to effects of anthelmintic formulations is at least partly due to an independent impact. Therefore, co-formulants should be given greater consideration both in the design of ecotoxicological experiments and in environmental risk assessments.